(untitled) (ArtCultura, 2008)
O artigo trata do cinema mudo produzido em São Paulo no início do século XX, como uma forma de apropriação simbólica do espaço urbano pelos ítalo-paulistanos. Estes, após terem participado ativamente das companhias de teatro amador existentes na cidade, serão os pioneiros do cinema nascente, cujas bases encontram-se justamente na rica rede de trupes treatrais paulistanas. A problemática assim circunscrita permite ainda cruzar práticas sociais urbanas com as relações de gênero que as atravessam. Tudo isso num contexto urbano de profundas transformações onde tomam forma novas dinâmicas de ocupação do espaço. PALAVRAS-CHAVE: ítalo-paulistano(a)s; cidade; cinema. ABSTRACT The article is about silent movies produced in São Paulo in the beginning of the 20th century, as a way of symbolic appropriation of the urban space by Italian immigrants. After actively participating in the amateur companies existing in the city, these immigrants were the pioneers of the new-born cinema, whose basis lie precisely in the rich network of the São Paulo theater companies. The problem so delimited also permits to cross social urban practices with the gender relations within them. All of that in an urban context of deep transformations which take the form of new dynamics of space occupation. KEYWORDS: São Paulo Italian immigrants; city; cinema.